MOLECULAR MECHANISMS OF DEACTIVATION OF DENDRITIC CELLS IN PATIENTS WITH PULMONARY TUBERCULOSIS - Z. K. Khaitova (Бюллетень сибирской медицины, 2013)
We have investigated dendritic cells (DC), obtained by transformation from peripheral blood monocytes. We show the possible mechanisms of infringement of dendritic cells (DC) functional activity in patients with pulmonary tuberculosis (TB). Found that in patients with TB the number of DC, expressing TLR2, costimulation molecules CD86, is reduced, secretion of cytokine IL-12 changes. It is possible the mecha-nisms of deactivation DC mediated from effects of M. tuberculosis